Identity at the edge of the word: the phenomenon of terruqueo in cyberspace, forms and hegemonic representations - Mago, Bruno (2023)
This article analyzes one of the discriminatory discourses that has recently acquired special relevance in the Peruvian national context: cyberterruqueo. The aim is to carry out a descriptive analysis of the phenomenon —from the political-ideological and ethnic, racial and cultural perspectives—, and to study, in the context of cyberspace, the hegemonic representations that are discursively created with respect to certain sectors of the population. Methodologically, the study has an exploratory qualitative approach. The study of these representations was based on the occurrence of this phenomenon within the framework of the Twitter social network, and the data for the analysis were collected from Twitter. Among the results, it was found that cyberterruqueo functions as a tool of social annihilation and stigmatization that is based on negative representations in order to achieve the invalidation or delegitimization of certain sectors of the population and their demands and needs, in favor of the perpetuation and domination of a hegemonic sector or establishment and its agenda. The article concludes, in turn, that virtual space and the social interactions it comprises are a reflection of reality, and that it allows for the production, reproduction and socialization of certain hegemonic representations configured in the discourse.